2017
DOI: 10.15419/bmrat.v4i11.382
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between some biochemical and hematological changes in type 2 diabetes mellitus

Abstract: Introduction: The aim of this study was to investigate various biochemical and hematological parameters in patients with type 2 diabetes mellitus (T2DM) and compare those with non-diabetic subjects (control group). Subjects: The study was conducted on 405 subjects (ages ranging from 26-65 years old; sex matched) who were classified into two groups: diabetic (n=205 subjects; males-105, females-100) and non-diabetic  subjects (n=200; males-100, females-100). The study was carried out during the period of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Results of previous studies conducted by Wu et al. [14] and Al Shehri [1] align with those of our study that have revealed that Type 2 diabetes is associated with elevated HbA1c, cholesterol, triglyceride, LDL with lower HDL and shortened telomere length, compared to the control group. Hyperglycaemia and dyslipidaemia increase reactive oxygen species (ROS) from the mitochondrial electron transport chain in Type 2 diabetes and diabetes-associated complications.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results of previous studies conducted by Wu et al. [14] and Al Shehri [1] align with those of our study that have revealed that Type 2 diabetes is associated with elevated HbA1c, cholesterol, triglyceride, LDL with lower HDL and shortened telomere length, compared to the control group. Hyperglycaemia and dyslipidaemia increase reactive oxygen species (ROS) from the mitochondrial electron transport chain in Type 2 diabetes and diabetes-associated complications.…”
Section: Discussionsupporting
confidence: 92%
“…Many diseases have reached epidemic proportions worldwide, but among the most important is Type 2 diabetes mellitus [1]. A primary cause of diabetes is the lack of insulin secretion or its action, which leads to dyslipidaemia and other complications [2].…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical and haematological factors in type 2 diabetes mellitus patients and the controlled group was studied by Shehri in 2017 and found that type 2 diabetes mellitus patientsʼ biochemical and haematological characters are distinct from control subjects 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Daily swimming training can be beneficial effects on blood parameters in diabetics (12,21). Some studies showed that exercise activities have significantly improved hematocrit, hemoglobin levels and RBC count in pregnant women, athletes, patients with T2DM, and STZ induced diabetic (36,38). In diabetic animals and humans, a relative decrease in lymphocyte ratios in leukocyte types and an increase in neutrophil count were observed (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%